Enfermeiro: o simbólico da imprescindibilidade da formação de ser educador na prática da gestão assistencial - Melaragno, Ana Lygia Pires [UNIFESP] (2016)
This study was conducted with nine nurses who were undergraduates from a public university of São Paulo and worked in the same city in an institution specialized in pediatric oncology. The aim was to understand the meaning of being an educator and the relationship with the daily work and training through the perspective of these nurses. It is an exploratory study of qualitative approach, using Symbolic Interactionism as the theoretical and methodological framework. The data from the interviews were analyzed using the steps of Grounded Theory, which allowed the identification of the conceptual category "Nurse: the symbolic of the indispensability of training to be an educator in the practice of health care management?. Six selective categories have been identified: Forming a nurse educator; Being a nurse educator; Dedicating to be a nurse educator; Understanding educational activities; Identifying nursing, staff and institution models; Experiencing feelings of being a nurse educator. The development of being a nurse educator for the undergraduates during their education meant interacting with the users of basic care. On the subject of Collective Health Care, they apprehended the importance of the guidance that was given, which was essential to develop this practice in other stages. On the hospital care area, they realized that nurses needed to interact with the patients and their relatives, primarily with the pediatric population. The symbolic of being an educator was to exercise clinical reasoning, in which the full knowledge of the disease is indispensable. The training for the education of the nursing staff was perceived as a task of the internship in the Discipline of Nursing Administration, despite the importance verified on their performance. They value the educational institution and the rearguard of a university hospital regarded as a differentiator for their training. Being a nurse educator in the researched institution is a cause for satisfaction and the feeling of serving as a reference for the patient, their family and the staff. The educational activities developed by the undergraduates consisted of guidelines on nursing care, self-care, home care and interdisciplinary interaction. The study demonstrates that nurses need to develop educational skills since before graduation in order to feel more confident in operation, mainly in specialized institutions.